Cell volume regulation and aquaporins - Capurro, Claudia (2008)
In the recent years, the importance of the volume of a given cell has been accepted not only in defining its intracellular osmolality and its shape, but also in defining other cellular functions, such as transepithelial transport, cell migration, cell growth, cell death and the regulation of intracellular metabolism (35). Since most cells have to perform these physiological functions under a variable osmotic stress, cell volume must be carefully regulated. Based on the origin of the disturbance, cell volume changes are frequently classified into two categories: anisosmotic (alterations in extracellular solute concentration) and isosmotic (alterations in intracellular solute concentration) volume changes. Because of the relatively high permeability of the plasma membrane for water, any such gradient results in the immediate flow of water into or out of the cell causing cell swelling or shrinkage. To regulate cell volume, cells use channels and transport systems to flux osmolytes across the plasma membrane, followed by the obligatory movement of water. The current review reflects these developments and focuses on the contributions of aquaporins water channels in regulatory volume processes in a variety of cells.